Comparative toxicity of mono- and bifunctional alkylating homologues of sulphur mustard in human skin keratinocytes. (1st May 2017) - Sawyer, Thomas W.; McNeely, Karin; Louis, Kristen; Lecavalier, Pierre; Song, Yanfeng; Villanueva, Mercy; Clewley, Robin
Abstract: Sulphur mustard (bis(2-chloroethyl) sulphide; agent H) is a vesicant chemical warfare (CW) agent whose mechanism of action is not known with any certainty and for which there are no effective antidotes. It has a pronounced latent period before signs and symptoms of poisoning appear which it shares with the nitrogen mustards, and that differentiates it from other classes of vesicant agents. Sulphur mustard, the sulphur mustard CW agents Q (1, 2-bis(2-chloroethylthio) ethane) and T (1, 1 bis(2-chloroethylthioethyl) ether), the H partial hydrolysis product hemi-sulphur mustard (2-chloroethyl 2-hydroxyethyl sulphide; HSM), and the commercially available 2-chloroethyl ethyl sulphide (CEES) were characterized with respect to their toxicity in first passage cultures of proliferating human skin keratinocytes, the target cell of H-induced skin vesication. Agents H and T were equitoxic and half as toxic as agent Q. Hemi-sulphur mustard and CEES were approximately six times and seventeen times, respectively less cytotoxic than H. 2-Chloroethyl ethyl sulphide was only slightly less toxic in confluent cultures compared to actively proliferating cells. In contrast, the toxicity of H, Q, T and HSM significantly decreased as the cultures became confluent, paralleling the decreasing sensitivity of skin keratinocytes to H as they leave the basement membrane of the skin. The toxicity of CEES was maximal by 24 h. In contrast, the maximal toxicity of the other four agents occurred at 48 h, mirroring the latent period observed for these agents in vivo . The markedly different characteristics of toxicity between CEES and the other four test compounds indicate that it is likely that different mechanisms of action are operative between them. Caution should therefore be taken when interpreting the results of studies utilizing CEES as a simulant for the mechanistic study of H, or in the elucidation of medical countermeasures against this CW agent. It is also notable that the toxicity characteristics of the mono-alkylating HSM mirrors those of H, Q and T, suggesting that the bi-alkylating characteristics of these latter compounds may not play as large a role in their toxic effects as commonly thought.